ナンキョク ドライバレー チイキ ニ オケル エーロゾル ノ カガク セイブン ノウド - 中谷, 周; ナカヤ, シュウ; 増田, 宣泰; マスダ, ノリヤス; 鳥居, 信也; トリイ, ノブヤ; 鳥居, 鉄也; トリイ, テツヤ; Nakaya, Shyu; Masuda, Noriyasu; Torii, Nobuya; Torii, Tetsuya (1989)
P(論文) 南極ドライバレー地域ライト谷のバンダ基地, ロワーライトハットでエーロゾル試料をワットマンNo.41ろ紙(径=110mm)にハイボリウムエアーサンプラーを用い約40-150m^3の大気を吸引採取し, 中性子放射化分析法により化学成分濃度を測定した。エーロゾル中Al濃度を指標として土壌起源粒子濃度を求め, 土壌起源粒子の降下フラックスを求めた。降下フラックス16μg・(cm)^<-2>・a^<-1>は北太平洋でのセジメントトラップ実験による大気除去土壌粒子フラックスに相当するものであった。 Atmospheric aerosols were collected at Vanda Station and the Lower Wright Hut in the Dry Valleys area, South Victoria Land, Antarctica, on a 110mm diameter Whatman No. 41 filter paper using a high volume air sampler with a handy type generator. Air sampling volumes ranged from 40-150m^3. Concentrations of chemical elements were determined with a neutron activation method. Atmospheric mineral dust flux is estimated at 16μg・(cm)^<-2>・a^<-1> based on Al concentration of aerosol. This atmospheric flux to the Dry Valleys area is comparable to the downward flux of aluminosilicate materials in the water column of the North Pacific Ocean as measured by sediment traps. departmental bulletin paper